2002
DOI: 10.1099/0022-1317-83-6-1331
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the principal serological immunodeterminants of African swine fever virus by screening a virus cDNA library with antibody

Abstract: Protective immunity to African swine fever virus (ASFV) may involve a combination of both serological and cellular mechanisms. This work is focused on the identification of the possible relevant serological immunodeterminants of immunity. Thus, 14 serological immunodeterminants of ASFV have been characterized by exhaustive screening of a representative lambda phage cDNA expression library of the tissue culture-adapted Ba71V strain of ASFV. The library was constructed using RNA extracted from Vero cells infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 35 publications
1
62
0
Order By: Relevance
“…Thus, the only unarguable proof for an antigen to become a real vaccine candidate comes from its potential to clinically protect individuals (60). Confirming this theory, in vitro screening of both B-and T-cell epitopes identified ASFV determinants that, however, failed to induce any measurable protection (61,62). This is most probably the main reason why there are only a few reports identifying optimal vaccine candidates screened from successful ELI libraries obtained from large and complex pathogens (63).…”
Section: Fig 4 Kinetics Of the Detection Of Ifn-␣ (A) And Tnf-␣ (B) Imentioning
confidence: 87%
“…Thus, the only unarguable proof for an antigen to become a real vaccine candidate comes from its potential to clinically protect individuals (60). Confirming this theory, in vitro screening of both B-and T-cell epitopes identified ASFV determinants that, however, failed to induce any measurable protection (61,62). This is most probably the main reason why there are only a few reports identifying optimal vaccine candidates screened from successful ELI libraries obtained from large and complex pathogens (63).…”
Section: Fig 4 Kinetics Of the Detection Of Ifn-␣ (A) And Tnf-␣ (B) Imentioning
confidence: 87%
“…Most probably, the assay takes advantage of specific biological attributes associated with the p30. On one hand, p30 as a main ASFV- induced protein which is incorporated in the virus particle carries strong immunogenic determinants and consequently represents a very efficient inducer of humoral responses (7,8,10). On the other hand, this protein is expressed and secreted at early times after infection (1,21), which would explain its rapid immune recognition after the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have demonstrated that recombinant viral proteins can give improved specificity and sensitivity when they are applied to the analysis of European field sera (9,19,22). In previous studies, 12 serological immunodeterminants of ASFV were characterized by exhaustive screening of a representative lambda phage cDNA expression library of the tissue culture-adapted Ba71V isolate of ASFV for antibodies (12). These included four proteins encoded by previously unassigned open reading frames (ORFs) (B602L, C44L, CP312R, and K205R), as well as some of the more well studied structural proteins (pA104R, p10, p32, p54, and p73) and three enzymes (RNA reductase, DNA ligase, and thymidine kinase).…”
mentioning
confidence: 99%